The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.archoralbio.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis antigens differently participate in the proliferation and cell death of human PBMC

Abstract: The inhibitory effect of cell proliferation caused by Pg LPS and HmuY protein is not observed when these antigens comprise Pg extract. Despite induced apoptosis, some still unknown mechanism determines the inflammatory outcome in cell death stimulated by HmuY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
1
10
0
3
Order By: Relevance
“…Recent data [25] has shown that P. gingivalis total antigens, as well as purified recombinant P. gingivalis HmuY, stimulate late apoptosis in PBMCs derived from CP patients. This finding suggests that although the protein is capable of signaling the apoptotic pathway, the stimulated cell is unable to terminate the apoptotic process that leads to cell death, thereby secondary necrosis is the resulting mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent data [25] has shown that P. gingivalis total antigens, as well as purified recombinant P. gingivalis HmuY, stimulate late apoptosis in PBMCs derived from CP patients. This finding suggests that although the protein is capable of signaling the apoptotic pathway, the stimulated cell is unable to terminate the apoptotic process that leads to cell death, thereby secondary necrosis is the resulting mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations have been done to confirm or refute these preliminary findings. It’s important to emphasize that the concentrations employed for each antigen was previously tested [6,25,29]. In this study, it was used 2.5 μg/mL of HmuY versus 0.5 μg/mL of crude extract (5fold more of the recombinant protein).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(27) Tem sido observado que HmuY consiste num fator de virulência importante, levando à inibição da proliferação celular; indução de apoptose tardia, por estimular a expressão de Bcl-2; (16) e indução de necrose em Células Mononucleares de Sangue Periférico de indivíduos com periodontite crônica. (28)…”
Section: Doença Periodontal: Dos Primórdios à Classificação Atualunclassified
“…Other molecules derived from P. gingivalis also have the capacity to modulate the immune response in peripheral blood mononuclear cells (PBMC) . Among them is HmuY protein, which is capable of inducing increased levels of IL‐1β and IL‐10 and inhibiting production of IL‐8 .…”
Section: Introductionmentioning
confidence: 99%